High-performance polygon rendering - Akeley, Kurt; Jermoluk, Tom (SIGGRAPH '88: Proceedings of the 15th annual conference on Computer graphics and interactive techniques, 1988)
This paper describes a system architecture for realtime display of shaded polygons. Performance of 100,000 lighted, 4-sided polygons per second is achieved. Vectors and points draw at the rate of 400,000 per second. High-speed pan and zoom, alpha blending, realtime video input, and antialiased lines are supported. The architecture heavily leverages parallelism in several forms: pipeline, vector, and array processing. It is unique in providing efficient and balanced graphics that support interactive design and manipulation of solid models. After an overview of algorithms and computational requirements, we describe the details of the implementation. Finally, the unique features enabled by the architecture are highlighted.